Creating academic structures to promote nursing's role in global health policy. (4th January 2017) - Gimbel, S.; Kohler, P.; Mitchell, P.; Emami, A.
Abstract : Aim: We highlight key components of emerging academic structures in global health nursing and explain how this investment can expand nursing's broader engagement in global health policy development. Background: Engaging nursing in global health policy development is vital to ensure the scale‐up of effective health programmes. Globally, nurses promote development of interprofessional healthcare teams who are responsible for translating sound global health policy and evidence‐based programming into practice. However, the role of nurses within policy forums and on influential decision‐making bodies within the global health space remains limited, which reinforces suboptimal global health policy implementation. Introduction: Investment in globally engaged academic structures is an important way to expand participation of nursing in global health policy development. Sources of evidence: A review of the current knowledge and substantive findings related to academic structures promoting global health nursing was conducted, and included a directed search of institutional websites, related grey and peer‐reviewed literature, and communication with top‐tier schools of nursing in the United States, to identify specific developments in global health nursing academic structures. Discussion/Conclusion: Effective academic structures promoting global health nursing include a framework of four critical components – Research, Education, Policy and Partnership. Academic structure type and core activities vary depending on institutional priorities. Implications for nursing, health and social policy: Increasingly, global health research, driven by individual nursing investigators, is expanding; however, in order to translate these advances into expanded involvement in global health policy development, academic structures within schools of nursing need to systematically expand educational opportunities, bolster research capacity and promote partnership with policymakers.